Point of Selection of Working Adult to Further Their Study in Higher Education Institutions: Evidence from Pahang State of Malaysia - Noor Elisurianie, Salehudin; Kamaazura, Abu Bakar; Ahmad Shahnun, Ibrahim (Universiti Malaysia Pahang, 2016)
Various initiatives have been taken to educate future young graduates, without denying the significance of working adult’s perception towards the selection and opportunity offered by Higher Education Institutions. Thus, this research was conducted to determine the factors of choosing the right Higher Education Institution among working adults, and the potential of the institutions available in Pahang State. The method used for data collection within the study is the questionnaire survey which deals with potential/future working adults. The questionnaires were distributed to various industries in Pahang area and the data set used for the analysis consists of 136 respondents. All identifying information; namely age, gender, race, and the highest level of education had been recorded as independent variables. Implication of this research will determine the intention of working adult in pursuing the offered program, predict the interest of working adult, and fulfil the industry’s needs. In conclusion, this study presents Higher Education Institutions as educational players for the sustainable growth of higher education in Pahang State.